Machine Learning Using TensorFlow Cookbook : Over 60 recipes on machine learning using deep learning solutions from Kaggle Masters and Google Developer Experts /: Over 60 recipes on machine learning using deep learning solutions from Kaggle Masters and Google Developer Experts. (2021) - Audevart, Alexia; Banachewicz, Konrad; Massaron, Luca
No abstract available